PENGARUH FASILITAS BELAJAR TERHADAP HASIL BELAJAR SISWA KELAS X IIS DAN XI IIS PADA MATA PELAJARAN EKONOMI DI SMA NEGERI 1 PEKANBARU - Anggraini, Ratih; Sumarno, Sumarno; Indrawati, Henny (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract : This research was conducted with the aim to find out the influence of learning facilities against the learning outcomes of students of class X and XI IIS IIS on economic subjects in SMA Negeri 1 Pekanbaru. The population in this research is the whole grade X and XI IIS IIS as many as 120 students and a sample that will be scrutinized as much as 55 students. Data collection using observation, questionnaires and documentation. Data analysis using linear regression analysis. The results showed that the learning facility influence on the results of the study. The influence of learning facilities at the school against results of a study of 0.686 and influence home study facilities against the learning outcomes of 1.050. The simultaneous learning facility influence on student learning outcomes with the determination of 45.5%.Keywords: Learning Facilities at school, Learning Facilities at Home, the results of the Study